Urban Development at Mid-Late Early Bronze Age Titriș Höyük in Southeastern Anatolia - Matney, Timothy (Bulletin of ASOR, 1995)
This article examines the role of Early Dynastic III and Akkadian period imperial ambitions of southern Mesopotamian states in shaping the initial process of urbanization in the upper Euphrates River Basin, encompassing portions of southeastern Turkey and northern Syria during the latter half of the third millennium B. C. Evidence is drawn primarily from recent excavations at the site of Titriș Höyük, capital of a small city-state that developed and collapsed in southeastern Turkey between the mid- and late Early Bronze Age (ca. 2600/2500-2400 and 2400-2100 B. C., respectively). The article investigates site morphology, organization of space, rate of urban growth and decline, and evidence for contacts with southern Mesopotamia. The genesis and growth of Titriș as an Early Bronze Age capital may be best understood as an opportunistic response by an indigenous polity benefiting from intensified trading contacts in the second half of the third millennium B. C. between the resource-starved alluvial lowlands of southern Mesopotamia and communities in the resource-rich areas of highland Anatolia.